Bringing taxonomy to life: development of online learning tools for binomial nomenclature in high school - Usyriyah, Laelatut; Sugianto, Sugianto; Hamidah, Idah (Nashir Al-Kutub Indonesia, 2025)
Students often experience difficulties in understanding and memorizing the Latin-based binomial nomenclature due to the complexity and diversity of biological terms. This research aims to develop and assess the feasibility of an online media platform based on artificial intelligence and hosted via Blogspot for learning binomial nomenclature among high school students. The study employed a Research and Development (R&D) approach using the 4D model: Define, Design, Develop, and Disseminate. The product underwent expert validation by subject matter and media specialists, as well as limited and large-scale trials involving students from SMAN 2 Indramayu. Validation by material experts yielded an average score of 4.6, categorized as